2022
DOI: 10.3390/toxins14100662
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Adverse Events Associated with Bee Venom Pharmacopuncture in Patients Hospitalized in a Korean Hospital: A Retrospective Chart Review Study

Abstract: In bee venom pharmacopuncture (BVP), bee venom isolated from the venom sac of bees is injected into the acupoint or muscle associated with a disease. However, the histamine component in bee venom can cause adverse events; therefore, attention is required for BVP use. This study investigated the frequency, severity and characteristics of patients developing BVP-associated adverse events. The medical records of patients treated with BVP at Kyung Hee University Korean Medicine Hospital between 1 January 2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Retrospective chart analysis revealed that the incidence of bee venom-related systemic immune responses is 0.02–0.234% in clinical practice. 35 , 36 A systematic literature review indicated that bee venom pharmacopuncture increased the relative risk of AEs by 2.6 times compared to normal saline injection. 37 Furthermore, this study reaffirmed the potential risk of a systemic hypersensitive immune response despite using sweet bee venom and its application.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective chart analysis revealed that the incidence of bee venom-related systemic immune responses is 0.02–0.234% in clinical practice. 35 , 36 A systematic literature review indicated that bee venom pharmacopuncture increased the relative risk of AEs by 2.6 times compared to normal saline injection. 37 Furthermore, this study reaffirmed the potential risk of a systemic hypersensitive immune response despite using sweet bee venom and its application.…”
Section: Discussionmentioning
confidence: 99%